2016
DOI: 10.1159/000481434
|View full text |Cite
|
Sign up to set email alerts
|

A New Baltic Population-Specific Human Genetic Marker in the PMCA4 Gene

Abstract: Objectives: The PMCA gene family consists of 4 genes and at least 21 splice variants; among these, the Ca2+ ATPase 4 (PMCA4) gene encodes a plasma membrane protein abundantly expressed in several tissues, including the kidney, heart, and sperm. Knockout of PMCA4 causes infertility due to immotile sperm in mouse models. We therefore investigated variants in this gene for potential association with infertility in groups of Estonian (n = 191) and Latvian (n = 92) men with reduced sperm motility. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Thus far, no gene mutations in PMCA4 have been identified in infertile patients. A study by Stavusis et al reported no significant association of PMCA4 gene variants in asthenozoospermic patients from Estonian and Latvian populations [ 140 ].…”
Section: Information From Knockout Mouse Modelsmentioning
confidence: 99%
“…Thus far, no gene mutations in PMCA4 have been identified in infertile patients. A study by Stavusis et al reported no significant association of PMCA4 gene variants in asthenozoospermic patients from Estonian and Latvian populations [ 140 ].…”
Section: Information From Knockout Mouse Modelsmentioning
confidence: 99%